Competição por mutualismos: hierarquia de dominância interespecífica mediada pela qualidade do recurso regulando interações formiga-planta - Souza, Roberth Fagundes de (2015)
Ants that collect nectar from plants bearing extrafloral nectaries (EFN) can defend them against the attacks of herbivores. Many cases of this food-for-protection mutualism have been described and the next step is to understand the mechanisms that structure these interactions. In this study, this issue was addressed through field observations and experiments on ant behaviour in studies compiled into five chapters. Specifically, we evaluated the plant\'s investment in attracting ants (nectar quality) and the competitive relationship between ants (resource dominance hierarchies) as structuring mechanisms of ant-plant interactions. The entire study took place in areas of the ecosystem known as Rupestrian Fields, located in Ouro Preto (Brazil), between June 2011 and March 2014. In Chapter 1, we observe that ant-plant interaction network in Rupestrian Fields is nested and generalized as expected for mutualisms, but differs from ant-hemipteran network, its ecological equivalent, despite both share ant species interactions. In Chapter 2, we delve into the study of the effect of resources in interaction frequency, and we showed that the quality more than quantity of nectar determines the pattern of interaction between plants (10 species) and ants (32 species), as well as the benefits of this interaction (conditional outcomes). In the Chapter 3, we focus on the ants to demonstrate, using paired encounters, that ants species are organized in dominance hierarchies based on aggressiveness. This hierarchies affects the numerical dominance based on territoriality and, more importantly, in the dominance of interactions and nectar. Keeping this line of thought, we demonstrated in Chapter 4 that not all ants that collect nectar really protect the plant against herbivores but only the ecological dominant and highly interacted species. Finally, we close the thesis demonstrating in Chapter 5 that the ant species interacted with plants during the day are not the same at night, but this diurnal-nocturnal turnover does not affect the structure of the interactions by only changing the dominant species. This study brings behavioural and empirical evidences on the importance of the identity of the ant species and its ecological dominance, as well the effect of the nectar quality, for the structure of ant-plant interactions and effectiveness of mutualisms.